Benefits and challenges associated with the timing of tracheostomy in critically ill patients: experience at a tertiary intensive care unit - Hajare, Priti S.; Havaldar, Rajesh Radhakrishna (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Prolonged intubation in intensive care units (ICU) leads to damage to the airways. Tracheostomy is performed with an aim to facilitate pulmonary toileting and also protect the upper airways from the associated ill effects of prolonged endotracheal intubation. The timing of this procedure is a matter of considerable debate and varies according to different centres. Methods: 50 patients were assessed. 34 belonged to the early group and 16 belonged to the late group. The study was carried out in the ICU of a tertiary care referral centre. The timing of occurrence of ventilator associated pneumonia (VAP), duration of ICU stay and duration of tracheostomy and the was compared between the early and late groups respectively. Results: It was found that early tracheostomy leads to reduced ICU stay and delayed occurrence of VAP. The results were statistically significant. Additionally, it was also observed in this study that early tracheostomy leads to reduced duration of tracheostomy as compared to the late group although not statistically significant. Conclusions: Due to large clinical heterogeneity amongst cases admitted to the ICU, the timing of tracheostomy is different in different centres. Hence, guidelines need to be formulated in order to perform tracheostomy in critically ill patients in order to prevent the demerits associated with late tracheostomy such as prolonged ICU stay, early occurrence of VAP and late decannulation. In addition to this, economic advantages also need to be considered as most of the population in developing countries do not have universal health insurance.